2016
DOI: 10.1371/journal.pone.0150515
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Production Is Critical for Sustaining the Expansion of CD5+ B and NKT Cells and Restraining Autoantibody Production in Congenic Lupus-Prone Mice

Abstract: The development and progression of systemic lupus erythematosus is mediated by the complex interaction of genetic and environmental factors. To decipher the genetics that contribute to pathogenesis and the production of pathogenic autoantibodies, our lab has focused on the generation of congenic lupus-prone mice derived from the New Zealand Black (NZB) strain. Previous work has shown that an NZB-derived chromosome 4 interval spanning 32 to 151 Mb led to expansion of CD5+ B and Natural Killer T (NKT) cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…It should be emphasized that the effects of IL-10 c-aAb are likely highly context-specific, as another previous study from our research group reported that IL-10 c-aAb were associated with increased risk of major adverse cardiovascular events (MACE) in kidney-transplanted patients, an outcome that is intrinsically linked to a pro-inflammatory environment [33]. Thus, though protective in regard to infections in healthy individuals, IL-10 c-aAb may constitute a risk factor for patients in whom excess inflammation may tip a balance towards adverse events such as organ transplant patients and autoimmune disease in general, again due to the cytokines' many immunoregulatory functions [34,35]. Conversely, c-aAb against pro-inflammatory cytokines IFNα and IL-1α have been linked to improved prognoses in autoimmune disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that the effects of IL-10 c-aAb are likely highly context-specific, as another previous study from our research group reported that IL-10 c-aAb were associated with increased risk of major adverse cardiovascular events (MACE) in kidney-transplanted patients, an outcome that is intrinsically linked to a pro-inflammatory environment [33]. Thus, though protective in regard to infections in healthy individuals, IL-10 c-aAb may constitute a risk factor for patients in whom excess inflammation may tip a balance towards adverse events such as organ transplant patients and autoimmune disease in general, again due to the cytokines' many immunoregulatory functions [34,35]. Conversely, c-aAb against pro-inflammatory cytokines IFNα and IL-1α have been linked to improved prognoses in autoimmune disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the NZB background, the presence of autocrine IL-10 by B1a cells was found to be critical for expansion to become lymphoma since IL-10 knockout strongly decreased CD5 + B lymphoma incidence (59). Furthermore, autocrine IL-10 prevented original autoantibody production by B1a cells in NZB mice (61). As shown here, ATA B lymphoma in C.B17 mice also showed high expression of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 can function to stimulate the immune system by increasing the frequency of cytotoxic CD8C T cells and natural killer cells depending on the other cytokines present within the tumor microenvironment (IL-2 for T cell activation and IL-19 for Natural killer cell activation). 26,27 The anti-tumor effects of IL-10 are also demonstrated as IL-10 modifies and efficiently regulates the quality of antigen presentation. 20 The effects of IL-10 within the primary tumor are modulated by the surrounding cytokine profile and expression of the protein can provide insights into approaches the tumor takes to skew the immune response to either anti-inflammatory or pro-inflammatory.…”
Section: Discussionmentioning
confidence: 99%